2019
DOI: 10.1002/elsc.201900133
|View full text |Cite
|
Sign up to set email alerts
|

Improved in vitro rooting in liquid culture using a two piece scaffold system

Abstract: Plant tissue culture techniques have been used to propagate horticultural crops at a commercial scale for more than three decades. However, due to the high cost it is generally only used for high value crops. To increase production efficiency and make micropropagation viable for a wider range of species, new approaches to address key steps of the process with high labor inputs need to be evaluated. For this study, a two‐piece scaffold system was designed, prototyped using 3D printing, and tested to physically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…In vitro production of primulic acid I and II from adventitious roots of Primula veris ssp. veris was established in liquid culture systems with agitation [ 26 ]. The main cause of the positive effects of liquid culture on phytochemical production is the close contact between the explants and the medium, thereby providing more available nutrients than solid culture [ 25 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro production of primulic acid I and II from adventitious roots of Primula veris ssp. veris was established in liquid culture systems with agitation [ 26 ]. The main cause of the positive effects of liquid culture on phytochemical production is the close contact between the explants and the medium, thereby providing more available nutrients than solid culture [ 25 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…These studies demonstrated that auxin can be used to establish in vitro root culture for phytochemical production, but the appropriate type and concentration of auxin for pokeweeds need to be studied. Additionally, root induction in liquid medium can promote root growth and the production of phytochemicals due to better nutrient circulation than solid medium [ 26 , 27 ]. Therefore, this study established appropriate medium states and plant growth regulators (PGRs) for in vitro pokeweed adventitious root induction from leaf explants, considering root growth and phytochemical parameters.…”
Section: Introductionmentioning
confidence: 99%
“…We also added a substantial amount of sucrose while culturing the scion-rootstock system., as it has been reported that increasing sucrose concentration increases the number and size of new leaves and lateral roots 23 . The use of liquid medium for culturing micrograft allowed easy culture handling and media replenishing, e cient nutrient absorption, and lesser oxidative stress on explant 24 . For rooting, we performed three biweekly subcultures on the rooting medium.…”
Section: Discussionmentioning
confidence: 99%
“…With willow, they provided excellent results in terms of shoot length and multiplication coefficients, but rapid root growth through holes and gaps created a root mesh that was a problem during subcultures. Shukla et al [ 58 ] reported the use of two plastic comb-shaped pieces that were placed at right angles, creating a surface with holes to insert the explants; they claimed their design can be pulled apart in such a way that allows the plants to be removed from the bioreactor without damaging the roots. These authors evaluated its suitability for rooting woody plants using CIS without aeration or a rocker-based TIS.…”
Section: Discussionmentioning
confidence: 99%